2020
DOI: 10.21776/ub.hsj.2020.001.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytosis as The Short-Term Predictor for Mortality in Acute Coronary Syndrome Patients Undergoing Percutaneous Coronary Intervention

Abstract: Background: In daily clinical practice, leukocyte count is the most common and simple inflammation parameter. Moreover, its role in predicting acute coronary syndrome (ACS) patients' clinical outcomes and prognosis is still conflicting. This study aimed to assess the role of leukocytosis as the predictor of mortality in ACS patients undergoing percutaneous coronary intervention (PCI). Method: This single-center retrospective cohort study used the STEMI registry data in Saiful Anwar General Hospital, Malang, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…WBC and NEU were found to have an acceptable discriminative power for predicting ventricular rhythm disturbances in ACS patients and in patients treated with PCI. Rahimi et al in a multicenter study revealed that the only predictor for malignant ventricular arrhythmia in NSTEMI patients treated with early invasive strategy was WBC [29].…”
Section: Discussionmentioning
confidence: 99%
“…WBC and NEU were found to have an acceptable discriminative power for predicting ventricular rhythm disturbances in ACS patients and in patients treated with PCI. Rahimi et al in a multicenter study revealed that the only predictor for malignant ventricular arrhythmia in NSTEMI patients treated with early invasive strategy was WBC [29].…”
Section: Discussionmentioning
confidence: 99%